Evaluasi Pengalaman Pengguna E-Learning SMAN 90 Jakarta menggunakan Technique for User Experience Evaluation in E-Learning (TUXEL) - Muhammad Daffa Arga; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Learning Management System (LMS) is an information system that developed in order to support the learning process, including distribution of education materials and collaboration between student and educators. From interviews that conducted with students of SMAN 90 Jakarta, several problems were found in the LMS including features that could not be used and the LMS have never been evaluated before. The purpose of this research is to discover any user experience and usability issue on LMS using the TUXEL method. The retrieval data process is using three questionnaires, namely: general usability inspection, pedagogic usability inspection, and the last one is user experience evaluation that given to 10 respondents with the purposive sampling technique, prioritize the 11th grade student or the second year of school. The result of user experience evaluation got the average score of each scale, having a positive perception that it meets the condition above 0.8. Then researchers did the review of every items after sorting them by frequency. There are a total of 27 items sorted. The result of the study stated that there are 8 items found because the Moodle based LMS does not provide the related features, 6 items found because the school LMS does not use related features, and 13 items found because the student did not understand the features on LMS.